PENGARUH POLA LATIHAN SKIPPING DAN LATIHAN DRIBBLING STOP AND GO TERHADAP KECEPATAN DRIBBLING PEMAIN SEPAKBOLA USIA 14-15 TAHUN DI SEKOLAH SEPAKBOLA (SSB) NONGKOJAJAR MUDA KABUPATEN PASURUAN - Luji Hendar Prasojo; Supriyadi Supriyadi; Mulyani Surendra (Universitas Negeri Malang, 2017)
Abstract:. Mastery of dribbling technique skills for a football player is important. Without the mastery of good dribbling techniques then the goal of football games tend not to be reached maximally, as in the School Football (SSB) Nongkojajar Muda. This study aims to determine whether the pattern of skipping and dribbling exercise stop and go affects the speed dribbling football players aged 14-15 years in SSB Nongkojajar Young Pasuruan. Based on the result of pretest data and posttest data which have been analyzed using Statistical Package for Social Science (SPSS), the significance value is 0,000 which means H0 is rejected due to significant value (p) <α = 0,05. So it can be concluded that the pattern of skipping and dribbling exercise stop and go affects the speed dribbling football players aged 14-15 years in school football (SSB) Nongkojajar young.Keywords: Football, speed, skipping, dribbling, training pattern